2019
DOI: 10.1103/physrevb.100.205103
|View full text |Cite
|
Sign up to set email alerts
|

Quantum diffusion regime of charge transport in GdB6 caused by electron and lattice instability

Abstract: Based on accurate X-ray structure analysis of GdB 6 over the temperature range 85-300 K it has been shown that anomalously strong charge carrier scattering in the quantum diffusion regime of charge transport in this compound arises due to the formation of (i) dynamically coupled Gd 3+ dimers of about 3.3 Å in size with an energy of quasi-local oscillations ~ 7 -8 meV and (ii) dynamic charge stripes along the [001] direction of the cubic lattice. It has been revealed that anharmonic approximation is useful when… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As shown in Figure S3b, the zeta potential values measured at pH 7.4 were +12, −11.5, and +4.5 mV for bare Gd 10 B 6 NPs, F127–Gd 10 B 6 NPs and anti-EGFR-Gd 10 B 6 NPs, respectively, indicating that F127–Gd 10 B 6 NPs have a negatively charged surface, while bare Gd 10 B 6 NPs and anti-EGFR-Gd 10 B 6 NPs were positively charged. It was reported that in lanthanide hexaborides, it is commonly observed to have structural defects boron vacancies , especially in the presence of cubic lattice distortions, which can explain the positive surface charge of the Gd 10 B 6 nanoparticles. Gadolinium is a rare earth metal element with paramagnetic properties from unpaired electrons in the 4f orbitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S3b, the zeta potential values measured at pH 7.4 were +12, −11.5, and +4.5 mV for bare Gd 10 B 6 NPs, F127–Gd 10 B 6 NPs and anti-EGFR-Gd 10 B 6 NPs, respectively, indicating that F127–Gd 10 B 6 NPs have a negatively charged surface, while bare Gd 10 B 6 NPs and anti-EGFR-Gd 10 B 6 NPs were positively charged. It was reported that in lanthanide hexaborides, it is commonly observed to have structural defects boron vacancies , especially in the presence of cubic lattice distortions, which can explain the positive surface charge of the Gd 10 B 6 nanoparticles. Gadolinium is a rare earth metal element with paramagnetic properties from unpaired electrons in the 4f orbitals.…”
Section: Methodsmentioning
confidence: 99%
“…The FTIR absorption band at 1730 cm −1 of the F127-Gd 10 B 6 NPs is due to the stretching vibration of the carboxyl > C�O moieties from F127 (see the red curve in Figure S3a), which was shifted to a lower energy position of 1640 cm −1 upon conjugation with anti-EGFR, due to the keto−enol tautomerization. The FTIR bands at ∼3000 cm −1 for both F127-Gd 10 B 6 NPs and anti-EGFR-F127-Gd 82,83 especially in the presence of cubic lattice distortions, which can explain the positive surface charge of the Gd 10 B 6 nanoparticles. Gadolinium is a rare earth metal element with paramagnetic properties from unpaired electrons in the 4f orbitals.…”
Section: ■ Experimental Section Preparation and Characterization Of G...mentioning
confidence: 95%